Поняття й ознаки кадрового забезпечення Державної кримінально-виконавчої служби України та органів пробації - Свердлін, К. Ю.; Sverdlin, K. Yu. (Право і безпека. – 2023. – № 3 (90). – С. 126-134, 2023)
Розглянуто наявні підходи до визначення поняття кадрового забезпечення, виокремлено його основні ознаки та структурні елементи (складові), охарактеризовано зміст найбільш суттєвих властивостей. Звернено увагу на зв’язок і співвідношення кадрового забезпечення та кадрової політики, сформульовано визначення поняття кадрового забезпечення Державної кримінально-виконавчої служби України та уповноважених органів пробації. Наголошено на доцільності законодавчого закріплення поняття кадрового забезпечення органів і служб пенітенціарної системи України, а також на тому, що кадрове забезпечення має складну внутрішню структуру й управлінську природу. У зв’язку із цим наголошено на ролі засобів адміністративно-правового регулювання в організації та впорядкуванні відносин і процесів кадрового забезпечення в системі Державної кримінально-виконавчої служби України та уповноважених органів пробації.

The sphere of criminal penalties in our country has been undergoing reform for many years, and even today, in the context of Ukraine's opposition to the open full-scale military invasion of the russian federation, the work on transforming and improving the national penitentiary system has not stopped. The Ukrainian government, in cooperation with the international community, academics and civil society, has already taken a number of important steps to humanise the system. At the same time, some rather important problematic issues on this path have not yet received proper scientific and theoretical study or legislative regulation, in particular, the problem of staffing the State Criminal Executive Service of Ukraine and authorised probation bodies. The current Strategy for Reforming the Penitentiary System of Ukraine describes the problems of staffing in a rather superficial and fragmentary way, in fact, everything is reduced to its purpose and most important tasks. Obviously, this approach does not contribute to the improvement of the principles and mechanisms of this provision, nor to the efficiency and quality of the reform of the penitentiary system as a whole. In order to intensify research work in this area, the existing approaches to the definition of the concept of staffing have been considered, its main features and structural elements (components)

Рассмотрены имеющиеся подходы к определению понятия кадрового обеспечения, выделены его основные признаки и структурные элементы (составляющие), охарактеризовано содержание наиболее существенных свойств. Обращено внимание на связь и соотношение кадрового обеспечения и кадровой политики, сформулировано определение понятия кадрового обеспечения Государственной уголовно-исполнительной службы Украины и уполномоченных органов пробации.
The concept and features of staffing of the State Criminal Executive Service and probation bodies in Ukraine
Keywords: кадрове забезпечення; personnel support; кадровое обеспечение; кадрова політика; staffing policy; кадровая политика; пенітенціарна система; penitentiary system; пенитенциарная система; Державна кримінально-виконавча служба України; State Criminal Enforcement Service of Ukraine; Государственная уголовно-исполнительная служба Украины; органи пробації; probation authorities; органы пробации; адміністративно-правове регулювання; administrative and legal regulation; административно-правовое регулирование